Spatio-Temporal and Mechanical Analysis of Bench Press Phases: Barbell Kinematics and Dynamics Across Different Load Intensities - Miguel Rodal; Juan Manuel Franco-García; Jorge Carlos-Vivas; Francisco García-Muro San José; Arturo Pérez Gosálvez; Guillermo Charneco Salguero; Kostas Gianikellis; Jorge Pérez-Gómez (Applied Sciences)
This study aimed (1) to explore the spatio-temporal phases of the execution of the bench press (BP) exercise based on barbell acceleration and power; (2) to describe barbell velocity, acceleration, mechanical power, and mechanical work at different load intensities; and (3) to analyse differences in kinematic and mechanical parameters. Twenty-one men (21.4 ± 1.5 years; 175.1 ± 6.7 cm; 75.8 ± 7.7 kg; 1RM: 91.7 ± 13.7 kg) and nine women (21.7 ± 2.3 years; 163.3 ± 10.8 cm; 57.2 ± 6.8 kg; 1RM: 38.9 ± 10.5 kg) were evaluated during the eccentric and concentric phases of the BP at different load intervals: interval 1 (55 to 75% 1RM), interval 2 (>75 to 85% 1RM) and interval 3 (>85 to 100% 1RM). Both temporal (duration) and mechanical variables (velocity, acceleration, mechanical power and mechanical work of the barbell) were determined using the Xsens MVN Link System. Mechanical variables were compared among the three different intervals. Interval 3 displayed greater duration compared to intervals 1 and 2. Barbell acceleration and power showed four different phases of BP movement, corresponding to the second and third phases of the exercise, bar braking (eccentric) and bar acceleration (concentric), respectively; the first and fourth phases are mainly determined by gravity instead of muscle intervention. Velocity and acceleration were different among the three different intervals during both the eccentric and concentric phases (p < 0.05). No differences were found between intervals 2 and 3 in mechanical power or mechanical work during the eccentric phase. In conclusion, the BP exercise has four phases considering barbell acceleration and power. The maximum and mean velocity and acceleration during BP performance decrease as load intensity increases. Maximum and mean mechanical power, and mechanical work, decrease progressively in the second and third intervals for both the eccentric and concentric phases. Thus, kinematics and mechanical parameters vary depending on load intensities.